Kecerdasan Spiritual Pada Mahasiswa Pecinta Alam - Saputra, Dhanu, Taufik S.Psi., M.Si., Ph.D (2017)
Spiritual intelligence is the intelligence to deal with and solve the problem of meaning and value, namely the intelligence to put our behavior and life in the context of a broader and rich meaning and also includes intelligence in judging that one's actions or way of life are more meaningful than others. In this case, the phenomenon occurs among the activists of nature lovers, because the activists of nature lovers who are declared spiritually intelligent have not been able in meaning related to the values obtained while in the wild. The purpose of this research is to know the spiritual intelligence in the student of nature pecinnta. The sampling technique used in this research is purposive sampling. This research uses descriptive-qualitative approach of phenomenology, data collection using semi structured interview (semistructured interview) and descriptive observation. The data analysis technique used in this research is interactive technique consisting of 4 (four) stages: data collection, data reduction, data display, and conclusion. The results of research that has been done states that Spiritual Intelligence Student Nature Lovers are influenced by several aspects, among others, able to think flexibly and have a high awareness and able to face problems, know the values that exist and do not cause harm and always seek the truth. And influencing factors are gender, age and education.